Multiple roles of working women and psychological well-being - Sudhinta Sinha (Industrial Psychiatry Journal, 2017)
Background: Today, women's roles are emerging differently with new commitment and career oriented as well as commitment to families. So, this in turn leads to a number of stress and strain among working women. Aims and Objectives: The aim and objective of this study was to elucidate the work–family conflict on psychological well-being experienced by working women and to determine whether social support has beneficial role in the psychological well-being of the working women. Materials and Methods: Eighty-two women working in different professions from dual-earner family and 82 homemakers from traditional single-earner family were included in the study and assessed on the following: (1) Postgraduate Institute (PGI) Health Questionnaire and (2) PGI Social Support Questionnaire (SSQ) for the assessment of well-being and social support, respectively, and data were analyzed. Results: Working women scored lower on PGI Health Questionnaire than homemakers, which was statistically highly significant, indicating that working women had higher psychological well-being than homemakers or nonworking women. On the assessment of PGI and SSQ, scores revealed that women in dual-earner families perceived lower social support as compared to those of single-earner families. Conclusion: Employed women are more satisfied with their life than nonworking women, and the quality of home and work environments determines the impact of employment on the psychological well-being of working women in dual-earner families.